An evidence-based analysis of the management of N0 neck in patients with cancer of the parotid gland. Issue 10 (3rd October 2019) - Vartanian, Jose Guilherme; Gonçalves Filho, Joao; Kowalski, Luiz Paulo; Shah, Jatin P.; Suárez, Carlos; Rinaldo, Alessandra; De Bree, Remco; Rodrigo, Juan P; Hamoir, Marc; Takes, Robert P.; Mäkitie, Antti A.; Zbären, Peter; et al.
ABSTRACT: Introduction : Management of clinically negative neck (cN0) in patients with parotid gland cancer is controversial. Treatment options can include observation, elective neck dissection or elective radiotherapy. Areas covered : We addressed the treatment options for cN0 patients with parotid gland cancer. A literature review was undertaken to determine the optimal management of this group of patients. Expert opinion : Patients with parotid carcinoma and clinically negative neck have various options for their management. The analysis of tumor stage, histology and grade is essential to better define patients at risk for occult lymph node metastasis. These patients can be managed by surgery, radiotherapy or their combination, depending on the presence of risk factors, the moment at which such risk factors are detected, patient-related clinical conditions, medical provider expertise and institutional facilities.